Direct Preparation of Heteroaromatic Compounds from Alkenes - Donohoe, T; Kabeshov, M; Rathi, A; Smith, I (2010)
A series of aromatic heterocycles, thiazoles, imidazoles, and dimethoxyindoles, can be synthesised directly from alkenes via a ketoiodination-cyclisation protocol. The alkene starting materials are themselves easily accessible by many different and well-established approaches, and allow access to various aromatic heterocycles with excellent yields and regioselectivity. © Georg Thieme Verlag Stuttgart - New York.